PENGARUH PERCEIVED ORGANIZATIONAL CULTURE TERHADAP COUNTERPRODUCTIVE WORK BEHAVIOR DENGAN ROLE INDIVIDUAL PERSONALITY NARCISSISM SEBAGAI VARIABEL MODERASI DI MASA PANDEMI COVID-19 - Monica Sandra; Suharnomo Suharnomo (Diponegoro Journal of Management, 2022)
This study aims to analyze the effect of perceived organizational culture on counterproductive work behavior with the role of narcissistic individual personality as a moderating variable. This study uses the perception of organizational culture as an independent variable, counterproductive work behavior as the dependent variable, and the role of individual personality as a moderating variable. The population in this study were all active employees of Bank Jateng Main Branch Office, amounting to 90 people. This study takes the entire population as a sample or is called a census. Data obtained from questionnaires were processed and analyzed using SPSS and SmartPLS programs. The results showed that the perception of organizational culture had a negative and significant effect on counterproductive work behavior. While the results of the moderating variable, namely the role of the individual personality of narcissism, managed to become a moderating variable between perceptions of organizational culture and counterproductive work behavior.